Single-visit endodontic treatment under general anaesthesia in adult and adolescent patients with special needs: a systematic review - El-Sayed, Shirin; Petrovic, Jelena; Frese, Cornelia; Sekundo, Caroline (Odontology, 2024)
To improve dental care for individuals with special needs, it is crucial to understand the effectiveness of endodontic treatments under general anaesthesia. This systematic review explores the feasibility, prognostic factors, and outcomes of root canal treatment and pulpotomy performed under general anaesthesia in adult and adolescent patients with special needs. A comprehensive search of Cochrane Library and MEDLINE databases was conducted until July 2024. The quality of evidence was assessed using the Newcastle-Ottawa scale (NOS). Among the 637 initially identified studies, 5 met the inclusion criteria. Treatment outcomes, radiographic findings, and clinical survival rates were evaluated. Root canal treatment success rates ranged from 81.5 to 90% over a minimum observation period of 12 months. Survival rates varied from 87.7% (9 year cumulative survival rate) to 89.8% (5 year survival rate). One study showed a lower failure risk in endodontic treatment under general anaesthesia compared to local anaesthesia. Another study found no significant difference in root canal treatment quality between general and local anaesthesia. Influencing factors identified by multivariate regression analyses included soft diet, periodontal status, oral hygiene status, pulp vitality, and length of root canal filling. Limited evidence suggests that endodontic treatment under general anaesthesia is feasible and can yield favourable outcomes in patients with special needs. However, the scarcity of studies and concerns about publication bias and methodological limitations emphasize the need for further research.
Online veröffentlicht: 13. Dezember 2024
Gesehen am 03.03.2025